Features of an Electronic Transaction as Evidence in Court (Law, State and Telecommunications Review, 2022)
[Purpose] This article is aimed at revealing the theoretical features of an electronic transaction as evidence in the procedural and legal field of a judicial instance.[Methodology/Approach/Design] The leading method of studying this issue is a combination of materials and methods of scientific knowledge. The main one is the dialectical method, which was used during the entire study and is considered the basic one in all components of the work, which made it possible to analyse comprehensively the theoretical developments of domestic and foreign scientists, as well as to study the judicial practice of applying the regulatory framework in the evidentiary process and the practical activities of leading lawyers in the judicial process of using electronic evidence.[Findings] The relevance of this article is due to the increasing trend in the use of electronic transactions, as well as the use of the latter in court as evidence. So, the legal nature of electronic transactions is analysed here in detail, namely: the history of occurrence, approval by national legislation, methods and conditions of conclusion, as well as legal force in legal relations between individuals and legal entities, the methodological basis for the study of the concept of electronic transactions has been determined, and their sources of legal regulation of their existence have been identified. The article provides a list of characteristic features of electronic transactions, reveals the main methods of their conclusion, justifies the effectiveness of using electronic transactions in courts as an evidence base, identifies the main legal omissions and shortcomings of the regulatory framework.[Practical Implications] The materials of this article provide applied value in the course of the reform and improvement of procedural legislation, as well as the development of methodological manuals for training and skill development of practising jurists and lawyers.